ANALISIS PERSEPSI KONSUMEN TERHADAP VARIAN PRODUK DI ARONA FOOD KEMIRI KABUPATEN PURWOREJO - Mutsanna, Ahmad Syarif (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2024)
The rapid digitization has caused people to shift their buying habits from offline to online. In addition, the product marketing plan should take into account changes in the community, such as the marketing of MSME products in Purworejo Regency. This research was conducted to find out more about the effect of product variation on purchasing decisions at Arona Food candlenut either partially or simultaneously. The number of samples is 50 respondents selected a purposive sampling method. The instrument test uses validity and reliability tests. Data analysis techniques using validity test, reliability test and multiple linear regression test. The results showed that the chili and rebon product variants did not have a significant effect on purchasing decisions at Arona Food Kemiri. Meanwhile, peanut butter has a positive effect on purchasing decisions at Arona Food Kemiri. Based on the test results, it is also known that simultaneously there is a positive and significant influence between the peanut butter product variants on purchasing decisions at Arona Food Candlenut. It is imperative to enhance the quality of the chili pepper and the rebon project variants in order to influence purchase decisions at Arona Food Candlenut more effectively